Novel brain MRI abnormalities in Gitelman syndrome. Issue 5 (October 2015) - Beltagi, Ahmed El; Norbash, Alexander; Vattoth, Surjith
Gitelman syndrome is an autosomal recessive renal tubular disorder characterized by hypokalemic metabolic alkalosis, hypomagnesemia and hypocalciuria. The syndrome is caused by a defective thiazide-sensitive sodium chloride co-transporter in the distal convoluted tubules of the kidneys. Gitelman syndrome could be confused with Bartter syndrome; the main differentiating feature is the presence of low urinary calcium excretion in the former. Descriptions of neuroradiological imaging findings associated with Gitelman syndrome are very scarce in the literature and include basal ganglia calcification, idiopathic intracranial hypertension and sclerochoroidal calcification. Cauda equina syndrome-like presentation has been reported, but without any corresponding imaging findings on lumbar spine MRI. We report a 13-year-old male with Gitelman syndrome who presented with altered mental status following a fall and scalp laceration and unremarkable brain CT, followed during hospitalization by somnolence and seizures. Metabolically the patient demonstrated hypokalemia and hypomagnesemia. MRI demonstrated features of encephalopathy including predominantly right-sided cerebral hemispheric signal abnormality and cytotoxic edema, with bilateral symmetric involvement of the thalami, midbrain tegmentum and tectum and cerebellar dentate nuclei. MRI after five months obtained during a later episode of encephalopathy showed resolution of the signal abnormalities with setting in of brain atrophy and also areas of newly developed cytotoxic edema in the left thalamus, bilateral dorsal midbrain and right greater than left dentate nuclei. The described abnormalities, either recurrent or in isolation, have not previously been published in patients with Gitelman syndrome. We believe that the findings are due to alteration of respiratory chain function secondary to the metabolic derangement and hence have a similar imaging appearance as encephalopathy related to mitochondrial cytopathy or metabolic encephalopathy.